A photocatalytic mortar prepared by tourmaline and TiO2 treated recycled aggregates and its air-purifying performance. (June 2022) - Chen, Xue-Fei; Jiao, Chu-Jie
Abstract: Herein, the study conducted an experimental investigation on a green building material containing construction and demolition wastes (C&DWs), nano-titanium dioxides (NT), and nano-tourmaline powder (TP). C&DWs indicated recycled clay bricks that were further divided into recycled clay brick sand (RCBS) and recycled clay brick powder (RCBP). RCBS was used as the carrier to support NT and to prepare the composite photocatalyst by a soaking method, with the final product denoted as NT@RCBS. NT@RCBS was then used to replace nature river sands in the mortar by weight ratios of 0, 50, 100%; whilst the TP was blended into the mortar with dosages of 0, 1, 5, 10, 15 wt%. The compressive strength, the concentration of negative ions, and the NOx degradation of prepared mortars were determined. The research is aiming to prepare a functional mortar that can both degrade existing air pollution and actively purify air quality. Experimental results revealed that TP increased the compressive strength when the content was no higher than 15 wt%. Besides, 15 wt% TP, coupled with 100 wt% NT@RCBS was optimal in generating negative ions of 950 ion/(s·cc) equivalent to that in the fresh air defined by the World Health Organization (WHO). By a 3-d surface map plotted by the respond surface methodology (RSM), the NT@RCBS content and the humidity were both positively related to the concentration of negative ions. At last, the coexistence of TP and NT@RCBS boosted the NOx removal, with the highest value of c.a. 250 μmol/(h·m 2 ). The prepared C&DWs based air purifying mortar is expected to provide a feasible approach to concurrently alleviate the solid waste disposal problem and the air pollution problem in megacities.